2012
DOI: 10.2527/jas.2011-4523
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the use of sex-sorted sperm in timed artificial insemination programs for suckled beef cows1

Abstract: Three experiments were designed to evaluate methods to optimize the use of sex-sorted sperm in timed AI (TAI) programs for suckled beef cows. In all 3 experiments, suckled Bos indicus cows were synchronized using an intravaginal progesterone (P4) device during 8 d and a 2.0-mg injection of intramuscular estradiol benzoate (EB) at device insertion. The females received PG and eCG (300 IU) at P4 device removal and 1.0 mg of EB 24 h later. The cows were inseminated 60 to 64 h after P4 device withdrawal. All cows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
19
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 32 publications
5
19
0
3
Order By: Relevance
“…However, fertility was lower for cows in which the semen was deposited into the cervix [11]. Similarly, other authors using low doses of semen [10,44] or frozen sex-sorted semen [8,13,45] observed similar fertility level after depositing semen either into the uterine body or uterine horn.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…However, fertility was lower for cows in which the semen was deposited into the cervix [11]. Similarly, other authors using low doses of semen [10,44] or frozen sex-sorted semen [8,13,45] observed similar fertility level after depositing semen either into the uterine body or uterine horn.…”
Section: Discussionmentioning
confidence: 77%
“…Deposition of semen into the uterine horns has been proposed as an alternative method to the traditional deposition into the uterine body. However, comparison of these two techniques has produced surprisingly variable results with reports of deep-horn AI having no effect [7–13] or improving [14–16] fertility in cattle.…”
Section: Introductionmentioning
confidence: 99%
“…Perry et al (2008a,b) suggested that preovulatory concentrations of estradiol during standing estrus may modulate uterine pH to affect sperm transport. However, that study (Sá Filho et al, 2012) involved Bos indicus cows rather than Bos taurus cows as in our study. Our data differ somewhat from those of Sá Filho et al (2012), who reported that pregnancy rates following FTAI to sex-sorted semen were not significantly lower than pregnancy rates to conventional semen among cows that had not exhibited estrus by the standard FTAI time.…”
Section: Discussionmentioning
confidence: 97%
“…However, that study (Sá Filho et al, 2012) involved Bos indicus cows rather than Bos taurus cows as in our study. Administration of ECP or EB following progestin device removal in the study by Sá Filho et al (2012) likely provides an enhanced estradiol environment and may potentially alleviate some of the reduction in FTAI pregnancy rates when using sex-sorted semen in nonestrous cows. Jinks et al (2013) demonstrated that administration of ECP to postpartum cows 24 h before GnRHinduced ovulation of a small dominant follicle and FTAI resulted in increased pregnancy rates compared to cows that did not receive ECP.…”
Section: Discussionmentioning
confidence: 97%
“…Jeśli w programach inseminacji w ustalonym czasie (TAI) pęcherzyk dominujący (PD) był mniejszy od 9 mm, to wskaźnik zacieleń wynosił 31,2%, jeśli był większy od 9 mm -56,8%. Różnice te w odniesieniu do nasienia konwencjonalnego, niezależnie od rozmiarów PD były porównywalne (58). Nie zmienia to faktu, że mimo wykorzystania tych samych kryteriów wyboru krów do inseminacji (pęcherzyk dominujący 12-18 mm, wypływ klarownego śluzu) wyniki zacieleń po inseminacji nasieniem sortowanym były istotnie niższe niż w przypadku użycia nasienia konwencjonalnego (25,7% wobec 39%) (36).…”
unclassified